Effect of Technological Factors on some Properties of Composite tube with Epoxy Resin K-153 Matrix - Trung Thanh, Nguyen (VNU Journal of Science: Natural Sciences and Technology, 2019)
The tube is made of polymer composite material based on K-153 epoxy resin (K-153 epoxy resin is made from ED-20 epoxy resin modified by thiokol and oligomer acrylate), T-13 glassfiber, hardener polyethylenepolyaminemade by wrapping on machine. The effect of drying temperature on mechanical properties (tensile strength, flexural strength) of polymercomposite materialwas studied. The paper also mentions to select suitable hardener to beused for polymercomposite tube wrapping. The results show that the strength at break, flexural strength of polymercomposite material are changedmuch when changing wrapping angle. The drying temperature increases, the curing time of polymercomposite material is much reduced. The time to stabilize after drying also greatly affects the pressure resistance of polymer composite tubes. Keywords Polymercomposite, K-153, tensile strength, flexural strength, pressure resistance. References [1] M. J. Mochane, T. C. Mokhena, T. H. Mokhothu, Recent progress on natural fiber hybrid composites foradvanced applications: A review, eXPRESS Polymer Letters 13 (2) (2019) 159-198. [2] J. Kim, H. J. Yoon, K. Shin, A study on crushing behaviors of composite circular tubes with different reinforcing fibers, International Journal of Impact Engineering 38(4) (2014) 198-207. [3] T. D. Jagannatha1, G. Harish, Mechanical Properties of carbon/ glass fiber reinforced epoxy hybrid polymer composites, Journal of Reinforced Plastics and Composites 4 (2) (2015) 131–137. [4] Vitalii Bezgin, Agata Dudek, Composites based on high-molecular weigh epoxy resin modified with polysulfide rubber, Composite Theory and practice 17(2) (2017) 79-83. [5] Abdouss, Majid, Farajpour, Tohid, Derakhshani, Morteza, The Effect of Epoxy-Polysulfide Copolymer Curing Methods on Mechanical-Dynamical and Morphological Properties, Iran. J. Chem. Chem. Eng. 30(4) (2011) 37-44. [6] G. Devendhar Rao, K. Srinivasa Reddy, P. Raghavendra Rao, Mechanical properties of E-glass fiber reinforced epoxy composites with SnO2 and PTFE, International Journal of Emerging Research in Management and Technology 6 (7) (2017) 208-214. [7] Hu Dayong, Jialiang Yang, Experimental study on crushing characteristics of brittle fibre/epoxy hybrid composite tubes, International Journal of Crashworthiness 15(4) (2010) 401-412 . [8] G.U. Raju, S. Kumarappa, Experimental Study on Mechanicaland Thermal Properties of Epoxy Composites Filled with Agricultural Residue, Polymers from Renewable Resources 3 (3) (2012) 118–138.